Study the Inhibition Effect of Amoxicillin Drug for Corrosion of Carbon Steel in Saline Media (Baghdad Science Journal, 2022)
Potentiostatic polarization and weight loss methods have been used to investigate the corrosion behavior of carbon steel in sodium chloride solution at different concentrations (0.1, 0.4 and 0.6) M under the influence of temperatures ( 293, 298, 303, 308 and 313) K. The inhibition efficiency of the amoxicillin drug on carbon steel in 0.6 M NaCl has also been studied based on concentration and temperature. The corrosion rate showed that all salt concentrations ( NaCl solution) resulted in corrosion of carbon steel in varying ratio and 0.6 M of salt solution  was the highest rate (50.46 g/m².d). The results also indicate that the rate of corrosion increases at a temperature of 313 K.. Potentiodynamic polarization studies showed that the examined inhibitor suppress both anodic and cathodic process and behave as mixed type inhibitor. The adsorption of amoxicillin was found to obey Langmuir isotherm model. Arrhenius equation and transition state theory were used to calculate kinetic and thermodynamic parameter. Results obtained showed that corrosion reaction of carbon steel in NaCl is spontaneous and there is a good agreement between the data got from the both techniques employed. SEM analysis was performed to study the film persistency of the inhibitor.